Development of Contextual Models in Subjects of Islamic Education Based on Dalihan Na Tolu to Improve Student Critical Thinking - Aisyah, Siti; Effendi, Heri; Azmi, Faizul (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to produce a Contextual Model in the History Course of Dalihan Na Tolu-based Islamic Education to improve students' critical thinking. Research activities include the development of learning tools and instruments needed in learning. Basically this learning model is an innovative model in the History of Islamic Education Learning, the main princi-ple of learning is to promote the philosophical values ​​of Dalihan Na Tolu as a basis for learning with a collaborative system. The process of developing this contextual model invol-ves the development of components of the learning model including: (1) Syntax; (2) Social systems (patterns or rules that apply and collaborate, discuss, ask questions, submit ideas when solving problems); (3) Principles of management reactions (lecturer behavior is allowed in guiding student work, responding to student behavior, directing and responding to student opinions); (4) Class atmosphere support system (semester learning plan, student worksheets, textbooks, student activity sheets, learning outcomes tests). This type of research is a device development research using a 4-D model (Thiagarajan model) et al (1974: 5) which includes defining, planning, developing and disseminate stages. The subjects of this study were the odd semester V STKIP Tapanuli South history education study program for the academic year 2017/2018. The research data was obtained through: (1) observation sheet, (2) test of learning achievement ability, and (3) questionnaire. Data analysis techniques carried out include descriptive statistical data analysis and inference statistical analysis. This research activity has been carried out through several stages, such as analysis, planning, design, development, and implementation. The results of the study consisting of RPP, LKM and Textbooks were stated to be very valid in terms of the validation of learning tools by validators with RPS obtaining an average score of 3.81, gaining a score of 3.82, and Textbooks gaining a score of 3.79 . Based on the results of the study it can be concluded that the Constitutional Model on the History Course of Dalihan Na Tolu-based Islamic Education to improve critical thinking students of the odd semester V history of STKIP Tapanuli Selatan in the school year 2017/2018 consisting of RPS, and Textbooks was declared very valid Keywords: contextual model, PSPI, Dalihan Na Tolu, critical thinking ABSTRAK Penelitian ini bertujuan untuk menghasilkan Model Kontekstual Berbasis Dalihan Na Tolu dalam PSPI untuk meningkatkan berpikir kritis mahasiswa. Kegiatan riset meliputi pengem-bangan perangkat pembelajaran dan instrumen yang diperlukan dalam pembelajaran. Pada dasarnya Model pembelajaran ini merupakan model inovatif dalam Pembelajaran Sejarah Pendidikan Islam (PSPI), prinsip utama pembelajaran yaitu mengedepankan nilai-nilai filosifis Dalihan Na Tolu sebagai basis pembelajaran dengan sistem kolaborasi. Proses pengembangan model kontekstual ini melibatkan pengembangan komponen model pembela-jaran antara lain: (1) Sintaks; (2) Sistem sosial (pola atau aturan yang berlaku dan berkola-borasi, berdiskusi, bertanya, mengajukan ide ketika memecahkan masalah); (3) Prinsip reaksi pengelolaan (prilaku dosen yang diperbolehkan dalam membimbing kerja mahasiswa, merespon prilaku mahasiswa, mengarahkan dan menanggapi pendapat mahasiswa); (4) Sistem pendukung suasana kelas (rencana pembelajaran semester, buku ajar, lembar aktivitas mahasiswa, tes hasil belajar). Jenis penelitian ini merupakan penelitian pengembangan perangkat menggunakan model 4-D (model Thiagarajan) dkk (1974:5) meliputi tahap pendefenisian (define), tahap perencanaan (design), tahap pengembangan (develop) dan tahap penyebaran (disseminate). Subyek penelitian ini mahasiswa program studi pendidikan sejarah semester V ganjil STKIP Tapanuli Selatan tahun pelajaran 2017/2018. Data peneli-tian diperoleh melalui: (1) lembar observasi, (2) tes kemampuan prestasi belajar, dan (3) angket. Teknik analisis data yang dilakukan meliputi analisis data statistik deskriptif dan analisis statistik inferensi. Kegiatan penelitian ini telah dilakukan melalui beberapa tahap, seperti analisis, perencanaan, desain, pengembangan, dan implementasi. Hasil penelitian yang terdiri atas RPP, dan Buku Ajar dinyatakan sangat valid ditinjau dari hasil validasi perangkat pembelajaran oleh para validator dengan RPS memperoleh skor rata-rata 3,81, dan Buku Ajar memperoleh skor 3,79. Berdarsarkan hasil penelitian dapat disimpulkan Model Konstektual pada Mata Kuliah Sejarah Pendidikan Islam Berbasis Dalihan Na Tolu untuk meningkatkan berpikir kritis mahasiswa sejarah semester V ganjil STKIP Tapanuli Selatan tahun pelajaran 2017/2018 yang terdiri atas RPS, LKM dan Buku Ajar dinyatakan sangat valid. Kata kunci: model kontekstual, PSPI, Dalihan Na Tolu, berpikir kritis